Slit2 Prevents Neutrophil Recruitment and Renal Ischemia-Reperfusion Injury - Swasti Chaturvedi; Darren A. Yuen; Amandeep Bajwa; Yiwei Huang; Christiane Sokollik; Liping Huang; Grace Y. Lam; Soumitra Tole; Guang-Ying Liu; J Pan; Lauren Chan; Yaro Sokolskyy; et al. (2013)
Neutrophils recruited to the postischemic kidney contribute to the pathogenesis of ischemia-reperfusion injury (IRI), which is the most common cause of renal failure among hospitalized patients. The Slit family of secreted proteins inhibits chemotaxis of leukocytes by preventing activation of Rho-family GTPases, suggesting that members of this family might modulate the recruitment of neutrophils and the resulting IRI. Here, in static and microfluidic shear assays, Slit2 inhibited multiple steps required for the infiltration of neutrophils into tissue. Specifically, Slit2 blocked the capture and firm adhesion of human neutrophils to inflamed vascular endothelial barriers as well as their subsequent transmigration. To examine whether these observations were relevant to renal IRI, we administered Slit2 to mice before bilateral clamping of the renal pedicles. Assessed at 18 hours after reperfusion, Slit2 significantly inhibited renal tubular necrosis, neutrophil and macrophage infiltration, and rise in plasma creatinine. In vitro, Slit2 did not impair the protective functions of neutrophils, including phagocytosis and superoxide production, and did not inhibit neutrophils from killing the extracellular pathogen Staphylococcus aureus. In vivo, administration of Slit2 did not attenuate neutrophil recruitment or bacterial clearance in mice with ascending Escherichia coli urinary tract infections and did not increase the bacterial load in the livers of mice infected with the intracellular pathogen Listeria monocytogenes. Collectively, these results suggest that Slit2 may hold promise as a strategy to combat renal IRI without compromising the protective innate immune response.